Observations of the views of university students on agricultural production - M. Helvacı; E. Cebeci; M. A. Aşkın (Труды по прикладной ботанике, генетике и селекции, 2022)
In this study, an attempt was made to examine the perspective of university students and their family members on the agricultural sector, the value they attach to agriculture and their own lands, the level of knowledge and awareness of the agricultural sector where they are engaged in production activities and make a living, and the importance they attribute to the sustainability of agriculture. In addition, the production activities of farmers and their membership in cooperatives or unions were also examined. The surveys conducted by interviewing a total of 200 participants representing university students and their family members within the scope of the research constituted the target material of this study. The obtained survey data were examined and tables containing frequency and percentage parameters were prepared and tried to be interpreted. According to the results of the research, a significant majority of the participants attribute importance to the integrity of the land and believe that agriculture is indispensable. Besides, considering the importance of the agricultural sector and the existing agricultural land, there is a substantial proportion of participants who do not see any harm in non-agricultural use of their lands and state that they will give up their lands in a possible situation.